A review of heat removal mechanism in concentrated PVT systems using beam splitter. (2022) - Kumar, Sushil; Thakur, Robin; Singhy, Arvind; Tripathi, R.K.; Sethi, Muneesh
Abstract: The dependency on solar energy is increasing day by day, so the PVT (Photovoltaic Thermal systems) have been developed in which thermal energy is not dissipated but harnessed using various heat removal mechanisms. The enhancement of Spectral Beam Splitting technique gives a solution to the problem that full spectrum is not useful for PV. Spectral beam splitting can be implemented through thin film reflection/transmission, conventional fluids absorption/transmission, nanofluid absorption and solar-cells reflection. To review the ongoing research in all these technologies is the main objective of this research paper.